2024
DOI: 10.1038/s41419-024-06619-4
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3 promote the progression of glioblastoma via inhibiting ferroptosis mediated by linc00857/miR-1290/GPX4 axis

Wenpeng Cao,
Ya He,
Jinzhi Lan
et al.

Abstract: The oncogenic properties of members belonging to the forkhead box (FOX) family have been extensively documented in different types of cancers. In this study, our objective was to investigate the impact of FOXP3 on glioblastoma multiforme (GBM) cells. By conducting a screen using a small hairpin RNA (shRNA) library, we discovered a significant association between FOXP3 and ferroptosis in GBM cells. Furthermore, we observed elevated levels of FOXP3 in both GBM tissues and cell lines, which correlated with a poor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…Among these DEMs, hsa-miR-1290, hsa-miR-145-5p, and hsa-miR-7977 have been previously identified as having a significant role in semen quality. Cao et al reported that FOXP3 activates the transcription of linc00857, which in turn increases the GPX4 mRNA stability via sponging hsa-miR-1290, thereby inhibiting ferroptosis [ 39 ]. On searching miRWalk, it was found that GPX4 is a gene target of hsa-miR-1290 (score = 0.846).…”
Section: Discussionmentioning
confidence: 99%
“…Among these DEMs, hsa-miR-1290, hsa-miR-145-5p, and hsa-miR-7977 have been previously identified as having a significant role in semen quality. Cao et al reported that FOXP3 activates the transcription of linc00857, which in turn increases the GPX4 mRNA stability via sponging hsa-miR-1290, thereby inhibiting ferroptosis [ 39 ]. On searching miRWalk, it was found that GPX4 is a gene target of hsa-miR-1290 (score = 0.846).…”
Section: Discussionmentioning
confidence: 99%